2001
DOI: 10.1007/s004170100324
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy in newly diagnosed middle-aged and elderly diabetic patients. Prevalence and interrelationship with microalbuminuria and triglycerides

Abstract: Background: The exact role of factors such as serum lipids, body mass index and (micro-)albuminuria as possible determinants of diabetic retinopathy remains to be determined. We have scrutinized the prevalence of diabetic retinopathy and its concomitants in terms of risk factors and other diabetic complications in newly diagnosed diabetic patients. Methods: A population-based sample of 1,251 newly diagnosed diabetic patients aged 40 years or over was established in general practice. Median age was 65.3 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 41 publications
0
9
2
Order By: Relevance
“…Though a very subtle connection has been reported between urinary albumin, DR and lipids [38], we did not find a significant association between serum lipids and albuminuria in our study. BMI was inversely related to macroalbuminuria, however, this finding may only reflect the worst nutritional state of patients with more advanced renal disease and not a causal relationship.…”
Section: Discussioncontrasting
confidence: 99%
“…Though a very subtle connection has been reported between urinary albumin, DR and lipids [38], we did not find a significant association between serum lipids and albuminuria in our study. BMI was inversely related to macroalbuminuria, however, this finding may only reflect the worst nutritional state of patients with more advanced renal disease and not a causal relationship.…”
Section: Discussioncontrasting
confidence: 99%
“…the results for diabetic retinopathy are in contrast to findings of other studies showing higher prevalence in Romania (14.37%) and Taiwan (25.5%). [11121314] the prevalence of diabetic retinopathy in newly diagnosed patients among various studies, Chennai Urban Rural Epidemiology Study (CURES) (5.1%) and United Kingdom Prospective Diabetes Study (UKPDS) (35%) is shown below in Figure 2. [1516]…”
Section: Discussionmentioning
confidence: 99%
“…The manifestation and the progression of DR are modified by multiple systemic factors such as arterial hypertension [1,6,8,10,11] , dyslipidaemia [4,6,8,12] , microalbuminuria [13] , insulin treatment [11] and ocular perfusion pressure [5] . However, their exact contribution to DR pathogenesis is in most cases unknown.…”
Section: Introductionmentioning
confidence: 99%